In Pursuit of Adult Progenitors of Thymic Epithelial Cells - Ishikawa, Tatsuya; Akiyama, Nobuko; Akiyama, Taishin (Frontiers in Immunology, 2021)
Peripheral T cells capable of discriminating between self and non-self antigens are the major components of a robust adaptive immune system. The development of such self-tolerant T cells is orchestrated by the thymus and fine-tuned by thymic epithelial cells (TECs), which are localized in the cortex (cortical TECs, cTECs) and medulla (medullary TECs, mTECs). cTECs and mTECs influence the maturation and the selection of T cells by promoting positive and negative selections of functional T cells, respectively. Recent advances in single cell RNA-sequencing technology have revealed a previously unknown degree of TEC heterogeneity, but we still lack a clear picture of the identify of TEC progenitors in the adult thymus. In this review, we describe both past and recent findings that shed light on the features of these elusive adult progenitors in the contexts of tissue homeostasis as well as recovery from damage to the stress-sensitive thymus.